2023
DOI: 10.1037/bne0000544
|View full text |Cite
|
Sign up to set email alerts
|

Pair housing does not alter incubation of craving, extinction, and reinstatement after heroin self-administration in female and male rats.

Abstract: Evidence suggests that single housing in rats acts as a chronic stressor, raising the possibilities that it contributes to measures of heroin craving and that pair housing ameliorates such measures. This study aimed to determine whether pair housing after heroin self-administration reduces the incubation of craving, extinction, and reinstatement of heroin seeking. Single-housed female and male Sprague-Dawley rats underwent daily 6-hr heroin self-administration, wherein active lever presses produced a heroin in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…This finding is consistent with other studies that have reported cue-elicited oxycodone-seeking responses using the extinction-reinstatement model of relapse in rats, although it is noteworthy that only males were used (Leri and Burns, 2005;Neelakantan et al, 2017;Nawarawong et al, 2019). Ours is therefore the first study to show cue-induced oxycodone seeking in female rats, an important but somewhat expected result given prior demonstrations of robust cue-induced reinstatement in female rats where opioids other than IV oxycodone were used as the primary reinforcer (Smethells et al, 2020;Bakhti-Suroosh et al, 2021;Malone et al, 2021;Nett and LaLumiere, 2022;Towers et al, 2022).…”
Section: Impact Of Sex and Estrous Cycle On Oxycodone-seeking Behaviorsupporting
confidence: 91%
“…This finding is consistent with other studies that have reported cue-elicited oxycodone-seeking responses using the extinction-reinstatement model of relapse in rats, although it is noteworthy that only males were used (Leri and Burns, 2005;Neelakantan et al, 2017;Nawarawong et al, 2019). Ours is therefore the first study to show cue-induced oxycodone seeking in female rats, an important but somewhat expected result given prior demonstrations of robust cue-induced reinstatement in female rats where opioids other than IV oxycodone were used as the primary reinforcer (Smethells et al, 2020;Bakhti-Suroosh et al, 2021;Malone et al, 2021;Nett and LaLumiere, 2022;Towers et al, 2022).…”
Section: Impact Of Sex and Estrous Cycle On Oxycodone-seeking Behaviorsupporting
confidence: 91%
“…This finding is consistent with other studies that have reported cue-elicited oxycodone-seeking responses using the extinction-reinstatement model of relapse in rats, although it is noteworthy that only males were used (Leri and Burns, 2005;Neelakantan et al, 2017;Nawarawong et al, 2019). Ours is therefore the first study to show cue-induced oxycodone seeking in female rats, an important but somewhat expected result given prior demonstrations of robust cue-induced reinstatement in female rats where opioids other than IV oxycodone were used as the primary reinforcer (Smethells et al, 2020;Bakhti-Suroosh et al, 2021;Malone et al, 2021;Nett and LaLumiere, 2022;Towers et al, 2022).…”
Section: Impact Of Sex and Estrous Cycle On Oxycodone-seeking Behaviormentioning
confidence: 77%